Study the impact of chronic obstructive pulmonary diseases on bone mineral density of biomass fuel smoke exposed population and its association with hs-CRP in Rural Haryana - Kamaljeet Singh,; Anand Agrawal,; Sunaina Kharb,; Rishi Rana, (Asian Journal of Medical Sciences, 2021)
Background: Chronic obstructive pulmonary disease (COPD) has deleterious systemic impact due to spillage of inflammatory mediators in the circulation though its association with highly sensitive C-reactive protein (hs-CRP) considers as surrogate marker of inflammation is not much explored hitherto. Aims and Objectives: This study aims to study the impact of COPD on bone mineral density (BMD) and its association with hs-CRP in rural population of Haryana. Materials and Methods: Tertiary care hospital-based case–control multigroup study conducted in the Department of Respiratory Medicine, BPSGMCW, Khanpur Kalan, Sonepat, Haryana, India. A total of 150 female study subjects included and comprise in three groups, G1: Biomass exposed COPD patients; G2: Biomass smoke exposed non-COPD subjects; and G3: Non-biomass exposed healthy control. Bone density measured using dual-energy X-ray absorptiometry, hs-CRP considers as surrogate marker of inflammation. Statistical software SPSS Version 23 used to measure Chi-square/Fisher’s exact test, Student’s t-test, and Pearson/Spearman’s rank correlation as test of significance, P<0.05 considered as statistically significant. Results: Mean total t-score of COPD subjects was −1.81±1.15, significantly lower than healthy control −0.66±1.69 (P=0.000), however, it is near to biomass exposed non-COPD subjects −1.74±1.14 (P=0.625). Odds ratio for the risk of osteoporosis in the lower limb among COPD group (Lt leg: 7.07; Rt leg: 4.51) was significantly high compare to other study subjects. Mean titer of hs-CRP (7.905±9.60; P<0.001) was significantly high in study group (G1), though its correlation with t-score was very weak (r=−0.024; P=0.867). Conclusion: COPD has significant impact on BMD of affected population predominantly on lower limb compare to other study subjects, however, no significant association was found with inflammatory biomarkers in the decrement of bone density despite high mean titer of hs-CRP among COPD patients.